Asymptotic theory for thin two-ply shells - Steigmann, David J. (Vietnam Journal of Mechanics, 2020)
We develop an asymptotic model for the finite-deformation, small-strain response of thin laminated shells composed of two perfectly bonded laminae that exhibit reflection symmetry of the material properties with respect to an interfacial surface. No a priori hypotheses are made concerning the kinematics of deformation. The asymptotic procedure culminates in a generalization of Koiter’s well-known shell theory to accommodate the laminated structure, and incorporates a rigorous limit model for pure bending.